Istikhdām Kitāb al-`Arabiyyah Baina Yaday Aulādinā Bi aṭ-Ṭarīqah al-Mubāsyarah Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā Mahārah al-Kalām (Dirāsah Ijrā’iyyah Bi MAN 4 Aceh Utara) - Al Fadil Muhammad; Ahmad Fauzi (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
MAN 4 Aceh Utara students learn a variety of subjects, including lessons to speak Arabic (Kalam). This lesson aims to make students be able to speak Arabic properly and correctly. However, in practice, students face many problems and difficult to Arabic speak resulted in the learning outcomes that have not reached the cut score (KKM). One of the reasons is that the teacher has not applied a good method and is in accordance with the student's condition, nor is there suitable learning media in learning. Researchers assume that the direct method and Arabiyah Baina Yadai Auladina text books can improve the skills of students in speaking. Therefore, Researchers to examine the use of Arabiyah Baina Yadai Auladina text books with a direct method to increase skills Arabic speaking (Classroom Action Research in MAN 4 Aceh Utara). The purpose of research is to determine the implementation of Arabiyah Baina Yadai Auladina text books and direct methods to improve the skills of students in Arabic speaking and its effect on students and student responses to this learning. Classroom action research methods is used in this study. Researchers collected data using observations, questionnaires and tests. Student of first grade who became the subject of research with the 20 students. The results show indicate that the implementation of learning is in accordance with the plan with a percentage of 57.69% (enough) in the first cycle and increased in the second cycle to 92.3% (very good). The ability of students in Arabic speaking increases after the application of this book and method. This is evident from the average score in the first cycle is 57.75 (enough) and in the second cycle increased is 79.25 (very good). The level of improvement in students' abilities or N-GAIN 1.03 is in the high interpretation. And finally, students responses to this application was positive